EVALUASI SISTEM INFORMASI AKUNTANSI PADA PENYUSUNAN LAPORAN PERHITUNGAN DAN PERTANGGUNGJAWABAN PADA KANTOR PELAYANAN KEKAYAAN NEGARA DAN LELANG SURAKARTA - Prihantoro, Wachid Mei (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2015)
This study aims to determine how the role of accounting information systems in the preparation of calculations and Accountability Reports On Kantor Pelayanan Kekayaan Negara dan Lelang (KPKNL) Surakarta, results of this study are expected to be used as inputs in the preparation of reports Calculation and Accountability ( PPJ ) that the preparation of reports PPJ can be run more effectively and as contributions to solving the problems faced by KPKNL the related statements PPJ. This research is a case study in KPKNL Surakarta, where there is a system weaknesses in the calculation and accountability reporting on KPKNL Surakarta. The scope of the study based on a survey of the preparation of reports by collecting qualitative and quantitative data with the determination of the subject. Determination of the subject based adjustment Sampling, which consists of three authorities. The data collection techniques questionnaires and interviews. Data were analyzed with Comparison Study. Results showed Preparation and Accountability report on the calculation of the Kantor Pelayanan Kekayaan Negara dan Lelang Surakarta been effective in accordance with the principles of internal control. Keywords: System, control, effective, accountable.